Sustainable Development Assessment on North Jakarta using Indicators and PLS-SEM - Lilyana Lilyana; Naufal Sanca Lovandhika; Rudy P. Tambunan; Suyud Warno Utomo; Teuku Yuri M. Zagloel; Lina Gozali (Indonesian Journal of Energy, 2019)
Indonesia, as the second longest coastline country in the world, contain a huge coastal area need to be managed. One way to manage coastal area is using monitoring systems, yet none of them has been effectively implemented in Indonesia. This research attempts to develop monitoring system using indicators. There were 105 indicators that chosen from references. Each of the indicators were filtered by scoring method and then be processed using PLS-SEM resulting 9 indicators and sustainability development monitoring model. Coastal Area of North Jakarta has been chosen as area to implementing the model since that area are dynamics and growing rapidly. Based on the model, coastal area of North Jakarta has good economic condition (62.2%), medium social condition (46.7%), and bad natural environment condition (38%). Sustainable development seems quite implemented in this area since the balance of Economic-Social-Natural Environment was on the medium and balanced category. By using GIS can be seen that the development that occurred in west side study area are better than middle or east side.